Long-Term Results of Partial Breast Irradiation After Breast-Conserving Surgery for Early Stage Breast Cancer: A Prospective Phase II Trial in China - Li, Yan; Shui, Lin; Wang, Xiaodong; Sun, Yu; Zhong, Renming; Shui, Pixian; Chen, Nianyong (Frontiers in Oncology, 2020)
Background     Partial breast radiotherapy (PBI) has emerged as an option after breast-conserving surgery for early-stage breast cancer patients. Methods    A total of 55 patients with early-stage breast cancer between 2009 and 2013 were enrolled in this single-institutional phase II prospective clinical trial. All patients received adjuvant PBI-IMRT after lumpectomy, with the prescription of 48 Gy in 12 fractions at 4 Gy per fraction, 5 days a week. The primary endpoint was ipsilateral breast tumor recurrence (IBTR), the other endpoints were a regional nodal failure (RNF), distant metastasis (DM) rate, disease-free survival (DFS), and overall survival (OS). These endpoints were used to evaluate clinical outcomes. The cosmetic effects and the late toxicity were assessed according to Harvard standard scale and CTCAE 3.0, respectively. Results In our cohorts, the median age was 45.60 years old (range 31 to 65 years) and 29.09% of these patients were post-menopause (n = 16). Most patients were T1 stage (65.45%) or N0 stage (70.91%). 80% of patients were ER-positive, 67.27% PR positive, and 61.82% HER2 negative. At the median follow-up of 9.25 years, RNF was 0% and IBTR occurred in only one patient (1.82%) to the chest wall. Except for one patient (1.82%) had DM to lung and pleura and died from disease progression, the remaining patients were alive at the end of the ten-year follow-up. The ten-year DFS and OS were 94.55% and 98.18%. One patient (1.82%) was diagnosed with endometrial cancer after PBI. Except for 9 patients who declined the cosmetic assessment, the rest of the 46 patients (83.64%) were all rated as good and well-satisfied with the appearance of the irradiated breast. No breast retraction and fibrosis were observed in any of the patients. Additionally, only 4 patients experienced grade 1 late toxicity (7.28%). None had grade 3 or higher late toxicity.   Conclusion This is the first study to report the ten-year results of PBI after breast-conserving surgery in Chinese patients. Our study suggested that PBI had durable local control and maintained good cosmetic outcomes with minimal late toxicity at long term follow up for the early-stage breast cancer patients.